On-Chip Broadband Mid-Infrared Supercontinuum Generation Based on Highly Nonlinear Chalcogenide Glass Waveguides - Xia, Di; Huang, Yufei; Zhang, Bin; Yang, Zelin; Zeng, Pingyang; Shang, Haiyan; Cheng, Huanjie; Liu, Linghao; Zhang, Mingjie; Zhu, Ying; Li, Zhaohui (Frontiers in Physics, 2021)
On-chip mid-infrared (MIR) supercontinuum generation (SCG) covering the molecular functional spectral region (3–12 μm) offers the advantages of robustness, simplicity, and compactness. Yet, the spectral range still cannot be expanded beyond 10 μm. In this study, on-chip ultrabroadband MIR SCG in a high numerical aperture chalcogenide (ChG) waveguide is numerically investigated. The ChG waveguide with a Ge-As-Se-Te core and Ge-Se upper and lower cladding is designed to optimize the nonlinear coefficients and dispersion profile. Assisted by dispersive wave generation in both short- and long-wavelength range, broadband SCG ranging from 2 to 13 µm is achieved. Besides, a fabrication scheme is proposed to realize precise manipulation of dispersion design. Such results demonstrate that such sources are suitable for compact, chip-integrated molecular spectroscopy applications.